On Generalized Suzuki Contraction Principles in \(C^*\)-Algebra Valued \(S_b\)-Metric Spaces with Applications - Prathigadapa, Anuradha; Chary, Varanasi Srinivas (Communications in Mathematics and Applications, 2026)
The aim of this study is to develop and establish novel unique fixed point (UFP) theorems within the framework of \(\mathbb{C}_{α}^{(φ, ψ)}\)-Suzuki contractions by employing two auxiliary functions \(φ\) and \(ψ\) in the context of admissible mappings on \(C^{*}\)-algebra-valued \(S_{b}\)-metric spaces (\(C^*\)-AV-\(S_b\)MS). Furthermore, the work intends to identify sufficient conditions ensuring the existence and uniqueness of fixed points and to illustrate the applicability of the obtained results to integral equations and homotopy through representative examples.
Keywords: \(\mathbb{C}_{α}^{(φ, ψ)}\)-suzuki contractive type mapping; FP and \(C^*\)-AV-\(S_b\)MS